Vortexes tune the chirality of graphene oxide and its non-covalent hosts. Issue 89 (23rd August 2016) - Di Mauro, A.; Randazzo, R.; Spanò, S. F.; Compagnini, G.; Gaeta, M.; D'Urso, L.; Paolesse, R.; Pomarico, G.; Di Natale, C.; Villari, V.; Micali, N.; Fragalà, M. E.; et al.
Abstract : The ability of vortexes to tune the chirality of graphene oxide in water sheds light on its complex supramolecular organization allowing for selective noncovalent deposition of a predetermined handedness on a solid surface. Abstract : Graphene oxide (GO) is one of the most appealing bidimensional materials able to interact non-covalently with achiral molecules and to act as chiral inducers. Vortexes can tune chirality and, consequently transfer a specific handedness to non-covalent host molecules, either when dispersed in water or when deposited on a solid surface.